Propuesta pedagógica: Arquitectura I - VI - Becker, Alejandro Daniel; Cavalli, Sergio Ricardo; Olivieri, Agustín (La Plata : s.n., 2014)
Contiene: Propuesta pedagógica y plan de actividades
Keywords: PROPUESTA PEDAGOGICA; ENSEÑANZA; EDUCACION UNIVERSITARIA; CONCURSOS; LA PLATA; FAU; 2014; ARQUITECTURA; BECKER-CAVALLI-OLIVIERI